Antifungal efficacy of botanicals against major postharvest pathogens of Kinnow mandarin and their use to maintain postharvest quality. (23rd May 2014) - Jhalegar, Md. Jameel; Sharma, Ram Roshan; Singh, Dinesh
<x content-type="archive" xml:space="preserve">Abstract</x> Introduction. Kinnow is an important citrus crop grown in India, which suffers from several postharvest diseases during storage. Hence, an attempt was made to combat such diseases with the botanicals Aloe vera, Eucalyptus and Ocimum on Kinnow mandarin to prolong its availability for a longer time. Materials and methods. For this, in vitro and in vivo studies were conducted. The poisoned food technique was used for in vitro studies, and, for in vivo studies, Kinnow fruit were pre-inoculated with pathogens (Penicillium digitatum and P. italicum), treated with different botanicals, then stored at (5 ± 1) °C temperature and 85–90% RH. Results and discussion. Our results indicated that all botanicals inhibited the growth (colony diameter) of both pathogens over untreated PDA plates, but the inhibition was the strongest by Aloe vera extracts. Similarly, under in vivo conditions, all botanicals influenced the decay incidence, decay loss, lesion diameter, respiration rate, ethylene evolution and physiological loss in weight, but Aloe vera was the most effective. All the botanicals were able to retain postharvest quality of Kinnow fruits without any adverse effect on quality parameters such as TSS, TA and ascorbic acid. Under in vivo conditions, the incidence of Penicillium italicum was higher than P. digitatum; however, it was the reverse under in vitro conditions. Conclusion. Thus, it is evident from our studies that botanicals have the potential to control green and blue mold without causing any injury or harmful effects on Kinnow mandarin; botanicals can be recommended as a safe method for extending its storage life while maintaining fruit quality at the same time.